Costs and benefits of ammonia and particulate matter abatement in German agriculture including interactions with greenhouse gas emissions. (December 2015) - Wagner, Susanne; Angenendt, Elisabeth; Beletskaya, Olga; Zeddies, Jürgen
Abstract: The abatement of ammonia (NH3 ) and particulate matter (PM) emissions in agriculture reduces damages to human health and biodiversity and provides benefits for society, but also imposes costs on farmers. As NH3 and PM emissions partly originate from the same activities as greenhouse gases, interactions may exist between NH3 and PM emission abatement and greenhouse gas emissions. This study is aimed at estimating the costs and benefits of NH3 and PM emission abatement measures, considering interactions with agricultural greenhouse gas emissions in Germany. We combined an economic-ecological farm model for estimating emission reductions and abatement costs with an integrated environmental impact assessment model for estimating the benefits for human health and biodiversity, with applications to three Federal States in Germany. We reasoned that benefits exceed costs and that synergies with greenhouse gas reduction exist. All NH3 and PM emission abatement measures affected greenhouse gases. In crop production, conservation tillage increased farmers' gross margins and reduced both PM emissions and, via soil carbon sequestration, also greenhouse gas emissions. The benefits depended on the soil type and its carbon sequestration potential, which differ across regions. The substitution of urea fertiliser for calcium ammonium nitrate reduced both NH3 and greenhouse gas emissions. In livestock production, the measures with the highest net benefits were chemical washers for exhaust-air purification, injection or cultivator manure application and concrete manure storage cover. Low-protein pig feeding increased farmers' gross margins and also achieved high net benefits, with the benefits of greenhouse gas emission reduction exceeding those of NH3 emission reduction. Low-protein poultry feeding and biofilters for air purification yielded negative net benefits and were therefore not recommended for implementation. The results confirm interactions of NH3 and PM emission abatement measures with greenhouse gas emissions and suggest that all relevant emission types be integrated in an analysis. Air pollution abatement and climate change mitigation have mainly been addressed in separate policies. Our results suggest that these policies are better integrated so as to stimulate synergies and to define the appropriate ambition level of emission reduction targets. Highlights: We pair economic-ecological farm modelling with an environmental impact assessment. Synergies and trade-offs among NH3 and PM emission abatement and greenhouse gases exist. Societal benefits exceed farmers' costs for most, but not all, abatement measures. Cost–benefit-analysis is useful for combining varying emission types and impacts. Suggests that agricultural, air quality and climate policies should be harmonised.